Psychometric Evaluation of the Nine-Item Problematic Internet Use Questionnaire (PIUQ-9) in Nine European Samples of Internet Users - Laconi, Stéphanie; Urbán, Róbert; Kaliszewska-Czeremska, Katarzyna; Kuss, Daria J.; Gnisci, Augusto; Sergi, Ida; Barke, Antonia; Jeromin, Franziska; Groth, Jarosław; Gamez-Guadix, Manuel; Ozcan, Neslihan Keser; Siomos, Konstantinos; et al. (Frontiers in Psychiatry, 2019)
Objectives: The nine-item Problematic Internet Use Questionnaire (PIUQ-9) is a brief self-report screening instrument for problematic internet use. The main objective of the present study was to explore the psychometric properties of the PIUQ-9 among nine different language-based samples of European internet users (Italian, German, French, Polish, Turkish, Hungarian, English, and Greek). Methods: The total sample comprised 5,593 internet users (38.1% men), aged between 18 and 87 years (M = 25.81; SD = 8.61). Via online recruitment, participants completed the PIUQ-9, the Brief Symptom Inventory (BSI) and items about time spent online. Results: Confirmatory factor analysis demonstrated that the bifactor model with one general factor (i.e., general problem) and two-specific factors (i.e., obsession and neglect + control disorder) yielded acceptable or good fit indices in all subsamples except for one. The common variance index in the bifactor model indicated that the general problem factor explained from 57.0 to 76.5% of common variance, which supports the presence of a strong global factor. According to the multiple indicators multiple causes (MIMIC) model, psychiatric symptoms had a moderate-to-strong direct effect on the general problem factor in all subsamples, ranging from β = 0.28 to β = 0.52 supporting the construct validity of the scale. Furthermore, in a majority of the subsamples, time spent online during the weekend had considerably higher effect sizes on the general problem factor than time spent online during weekdays. Conclusion: The present study highlights the appropriate psychometric properties of the PIUQ-9 across a number of European languages and cultures.